El localismo global de un clásico. Una visita a las Tradiciones de Ricardo Palma desde la teoría aristotélica de la mimesis y de la Weltliteratur de Goethe - Vega Cernuda, Miguel Ángel (2018)
In this paper we have glossed the universal value of Palma’s Traditions from the theory of Aristotelian mimesis and as realization of Goethe’s World literature. We have reviewed the presence of Palma in the international edition, criticism and translation.